Methodics of aviation engines diagnostics based on parameters measured at transitional regimes of engine operation - Дмитриев, С. А.; Путятин, Е. В.; Агарвал, Д.; Низар, Х. (Proceedings of National Aviation University, 2000)
Presented are operational experimental results of effect of different types of engine core defect on the dynamic characteristics of turbojet engine